(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
This symposium brings together researchers from across Europe to explore how practices in the context of school-based physical activity and physical education (PE) can be reimagined for a healthy, sustainable future, grounded in the concept of physical literacy (PL). In a context marked by physical inactivity and environmental challenges, this collection of studies emphasises the need for a transformative approach to PE that is culturally grounded, ecologically aware, and responsive to the evolving health needs of youth. The first presentation contextualises the current landscape of physical education by presenting a study that compared the curricula across Europe in January 2024. Experts from 40 European countries were asked to complete 15 cooperatively developed items, which operationalised all the spectrum between ‘PL-incompatible curricula’ and ‘PL-compatible curricula’. Aggregate scores quantified the degree of PL alignment and informed colour mapping as the basis for policy briefs sent to World Health Organization and UNESCO. The second contribution explores how PE can integrate holistic health paradigms, such as One Health, EcoHealth, and Planetary Health, into its pedagogical frameworks. The study positions PL as a vehicle for sustainable lifestyles, drawing on interdisciplinary insights and real-world examples to redefine PE’s mission in line with global ecological responsibility. In the third presentation, the recent overhaul of Estonia’s national PE curriculum is discussed. This large-scale educational reform places health and PL at its core, reflecting a major shift from sport-centred models towards learner-centred, holistic approaches. The process illustrates the political, pedagogical, and practical challenges of systemic change in national education policy. The symposium lead concludes this session through a presentation titled “Towards a Cross-Sectoral Global Monitoring for Quality Physical Activity Experiences?”. This presentation was used to open discussions and imagine a future for physical education research and policy across Europe. Together, these contributions offer a rich and diverse reflection on how PE can evolve to meet the dual challenges of promoting health and sustainability. The symposium advocates for a reconceptualisation of PE that is inclusive, ecologically grounded, and capable of nurturing PL and health-aware citizens from childhood through adulthood. Keywords: Physical literacy, curriculum, reform, sustainability, health education